Risk Factors For The Incidence Of Pulmonary Tuberculosis At Elly Uyo Health Center - lamria simanjuntak; Inriyanti Assa; Asriati Asriati; Frans Asmuruf; Katarina Tuturop; Natalia Adimuntja (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2023)
Tuberculosis is one of the top 10 causes of death in the world and the leading cause of death from a single infectious agent. The purpose of this study was to determine the risk factors for pulmonary tuberculosis in Elly Uyo Health Center in Jayapura City. This type of research is observational analytic with a case control approach. The case group was pulmonary tuberculosis patients and the control group was BTA negative patients at Elly Uyo Health Center. The sampling technique in the case group is saturated sampling and the control group is Purposive sampling. The number of samples was 60 samples with a ratio of 1: 3 consisting of 15 cases and 45 controls. The measuring instruments used were questionnaires, humidity measurements, lighting and ventilation then the data were analyzed univariately and bivariately. The results of the chi-square test showed a significant risk between occupancy densities (p-value = 0.000; OR=11,000; 95% CI=2.830-42.756), humidity (p-value=0.001; OR=8.857; 95% CI=2.154-36.418), lighting (p-value=0.012; OR=5.688; 95% CI=1,505-21,495) with the incidence of pulmonary tuberculosis. While there was an insignificant risk between contact history (pvalue = 0.153; OR=2,714; 95% CI=0.709-10.392), smoking habit (p-value=0.274; OR=1.938; 95% CI=0.587-6.399), ventilation area (p-value=0.527; OR=1.476; 95% CI=0.440-4.953) with the incidence of pulmonary tuberculosis at Elly Uyo Health Center in Jayapura City. It can be concluded that occupancy density, humidity and ventilation area are risk factors for pulmonary TB at the Elly Uyo Health Center in Jayapura City.